Integrating critical values of soil drivers for mitigating GHGs: An assessment in a sugarcane cropping system - Chalco Vera, Jorge Elías; Curti, Ramiro Nestor; Acreche, Martin Moises (Elsevier, 2022)
Agricultural practices can reduce emissions of greenhouse gases (GHG). The definition of management practices toward mitigating GHG emissions could gain accuracy by integrating critical values of soil variables related to GHG fluxes. The aim of this study was to combine critical values of soil variables determining groups of GHG fluxes with similar and/or opposite direction of carbon dioxide (CO2), nitrous oxide (N2O) and methane (CH4). We determined CO2, N2O, CH4 fluxes, soil temperature, gravimetric soil moisture (GSM), soil inorganic nitrogen (SIN), soil bulk density (SBD), soil porosity (P), and water-filled pore space (WFPS) monthly in three consecutive growing seasons in a sugarcane agroecosystem. The regression tree method defined groups of emission. Six terminal groups of CO2, N2O fluxes, and four for CH4 fluxes were determined. The critical values of soil variables that defined the terminal groups with the highest fluxes were soil temperature (>19 °C) and GSM (>35.2%) for CO2, GSM (>29.2%) and SIN (≤1.1 ppm) for N2O, and GSM (>24.9 °C), SBD (>0.98 g cm−3) and SIN (>1.82 ppm) for CH4. Trade-offs were found among GHGs: N2O emissions were high and CO2 emissions were low when GSM and soil temperature ranged from 29 to 35% and 14–19 °C, respectively (moderate values). CO2 emissions were high and N2O emissions were the lowest when GSM was equal or lower than 29.2% and soil temperature ranged from 19 to 21.3 °C. In this study, we highlight that management practices aimed to mitigate GHG fluxes should consider the integrated analysis of critical values of soil variables for GHGs together in order to avoid trade-offs.